Plasma and dietary carotenoids and vitamins A, C and E and risk of colon and rectal cancer in the European Prospective Investigation into Cancer and Nutrition. Issue 12 (14th May 2014) - Leenders, Max; Leufkens, Anke M.; Siersema, Peter D.; van Duijnhoven, Fränzel J.B.; Vrieling, Alina; Hulshof, Paul J.M.; van Gils, Carla H.; Overvad, Kim; Roswall, Nina; Kyrø, Cecilie; Boutron‐Ruault, Marie‐Christine; Fagerhazzi, Guy; et al.
<x xml:space="preserve">Abstract</x> Carotenoids and vitamins A, C and E are possibly associated with a reduced colorectal cancer (CRC) risk through antioxidative properties. The association of prediagnostic plasma concentrations and dietary consumption of carotenoids and vitamins A, C and E with the risk of colon and rectal cancer was examined in this case–control study, nested within the European Prospective Investigation into Cancer and Nutrition study. Plasma concentrations of carotenoids (α‐ and β‐carotene, canthaxanthin, β‐cryptoxanthin, lutein, lycopene, zeaxanthin) and vitamins A (retinol), C and E (α‐, β‐ and γ‐ and δ‐tocopherol) and dietary consumption of β‐carotene and vitamins A, C and E were determined in 898 colon cancer cases, 501 rectal cancer cases and 1, 399 matched controls. Multivariable conditional logistic regression models were performed to estimate incidence rate ratios (IRR) and corresponding 95% confidence intervals (CIs). An association was observed between higher prediagnostic plasma retinol concentration and a lower risk of colon cancer (IRR for highest quartile = 0.63, 95% CI: 0.46, 0.87, p for trend = 0.01), most notably proximal colon cancer (IRR for highest quartile = 0.46, 95% CI: 0.27, 0.77, p for trend = 0.01). Additionally, inverse associations for dietary β‐carotene and dietary vitamins C and E with (distal) colon cancer were observed. Although other associations were suggested, there seems little evidence for a role of these selected compounds in preventing CRC through their antioxidative properties.